Long-term clinical outcome after implantation of the self-expandable STENTYS stent in a large, multicenter cohort. Issue 7 (November 2017) - Gaede, Luise; Liebetrau, Christoph; Dörr, Oliver; Blumenstein, Johannes; Elsässer, Albrecht; Hamm, Christian W.; Möllmann, Helge; Schlundt, Christian; Nef, Holger M.; Achenbach, Stephan
Abstract : Objective: The objective of the study was to retrospectively evaluate the long-term clinical outcome after implantation of the self-expandable (SE) STENTYS stent in a large multicenter cohort. Background: Incomplete stent apposition is known to cause higher rates of myocardial infarction (MI) and stent thrombosis. Because of its self-expanding features, the SE STENTYS stent adapts to the vessel wall and is therefore expected to minimize malapposition and therefore the rates of MI and stent thrombosis. Patients and methods: Treatment with a total of 351 SE coronary stents was attempted in 314 patients of a cohort from three German institutions between 2011 and 2015. Technical success was achieved with 331/351 (94%) stents. Patients treated successfully with SE stents ( n =298) were followed up using the primary outcome measure of target lesion failure (TLF), a combined endpoint of cardiac mortality, recurrent target vessel MI, acute stent thrombosis, and clinically driven target lesion revascularization. Follow-up was complete in 268/298 (90%) patients with a median follow-up period of 2.5 (interquartile range: 1.4–3.3) years. Results: TLF occurred in 54/298 (18%) patients. Event rates were 7.5% for cardiac mortality, 11.6% for target vessel MI, and 5.2% for clinically driven target lesion revascularization. Acute stent thrombosis occurred in 2/298 (0.7%). Overall, stent thrombosis had an incidence of 2.6% within the follow-up period. ST-elevation MI at baseline ( P =0.02) and a dual antiplatelet therapy with clopidogrel for only 6 months ( P =0.04) were the only clinical factors linked to the absence of TLF. Conclusion: Technical success of SE coronary stent implantation in an all-comer cohort of patients was high, although the rate of TLF and stent thrombosis during long-term follow-up was also relatively high.